Quality of Drug Rehabilitation Services in Lembaga Peduli Anak Bangsa Samarinda - Nur Asiza; Sumarni Sumarni; Suwanto Suwanto (Indonesian Journal of Wiyata Health Administration (IJWHA), 2022)
Indonesia is no longer a transit country, but an area known as a potential drug dealer, even today Indonesia is considered a user of ecstasy. The purpose of the study was to look at the quality of drug rehabilitation services at the Samarinda Institute for Caring for the Nation's Children. This type of research is quantitative research with a cross-sectional study approach. The population and sample were all members/rehabilitation patients of the Samarinda City Nation Children's Care Institute, which numbered 32 people. The quality of narcotics rehabilitation services at the nation's children's care institutions is quite good because the supervision and improvement of service quality are also supervised by the National Narcotics Agency so that it can be consistent in its services.